BORING SPONGES DESTRUCTIVE TO ECONOMICALLY IMPORTANT MOLLUSCAN BEDS AND CORAL REEFS IN INDIAN SEAS - Thomas, P A (Indian Journal of Fisheries, 2011)
Systematics, description and distribution are given of 32 species of boringsponges from the Indian seas, the frequency of occurrence of which can varyfrom time to time as any one or more speci'js can at any lime causean outburst creating severe havoc in the economically important molluscan andcoral bedis and then disappear into a period of quiescent stage, while some othersmay continue to exhibit moderate incidence without causing any such deleteriouseffects.